Measurement of Radon Concentration in Drink and Well Water Samples for Selected Regions in Baghdad City - Jameel, Athraa Naji (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The concentration of radon gas in the samples for drinking water and wells in the same place from selected homes in which wells were built in the Hay-al-Bayaa region of Baghdad was measured, by using a CR-39 nuclear track detector. It turns out that the maximum value of the concentration of radon in drinking water was 3.83 Bq/L, and the lowest was 2.30 Bq/L. As for the estimation of radon gas concentration in well water samples, the highest value was 5.6 Bq/L, while the lowest one was 3.1 Bq/L. In order to assess the committed effective dose received by the public due to the inhalation of radon gas. The highest value of the annual effective dose in drinking water was recorded in Al-Bayaa region, which is equal to 14.30 μSv/y, while the minimum was recorded at 8.40 μSv/y. As it turns out, the annual effective dose in well water samples was 20.4 μSv/y, while the lower one was 11.57 μSv/y. All values for the radon concentration and the annual effective dose in the drinking and well water samples were below the World Health Organization’s recommended levels. The results showed that drinking water and wells were free of radioactive contamination in the studied area.